The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyt.2022.846838
|View full text |Cite
|
Sign up to set email alerts
|

Structural Deficits in the Frontotemporal Network Associated With Psychopathic Traits in Violent Offenders With Schizophrenia

Abstract: People with schizophrenia (SZ) are at increased risk of violence compared to the general population. However, the neural mechanisms of violent behavior in patients with SZ are still unclear due to the heterogeneity of the diseased population. In this study, we aimed to examine the neural correlates of violent behavior in SZ and to determine whether the structural deficits were related to psychopathic traits. A total of 113 participants, including 31 SZ patients with violent behavior (vSZ), 39 SZ patients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…Structural magnetic resonance imaging (sMRI) as an easy access, high resolution, and non-invasive imaging technique has been widely used to understand the neurobiology of violence in SCZ. Recent sMRI studies have confirmed significant alterations in multiple cerebral regions, in particular frontal and temporal lobes, in SCZ patients with violence [ 14 17 ]. For example, a study of cortical morphology showed reduced cortical thickness within the precentral, parietal, temporal, and fusiform cortex in SCZ patients with a history of violence [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structural magnetic resonance imaging (sMRI) as an easy access, high resolution, and non-invasive imaging technique has been widely used to understand the neurobiology of violence in SCZ. Recent sMRI studies have confirmed significant alterations in multiple cerebral regions, in particular frontal and temporal lobes, in SCZ patients with violence [ 14 17 ]. For example, a study of cortical morphology showed reduced cortical thickness within the precentral, parietal, temporal, and fusiform cortex in SCZ patients with a history of violence [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The volume alteration in regions of VSC appeared to be associated with impulsiveness, indicating that poor impulse control might play an important role in the neurobiological basis of violence in SCZ. Compared to prior studies, the whole-brain approach was superior to the analysis of specific isolated regions in the identification of regions associated with violence, as the analysis of isolated regions could be insufficient to reveal the neurobiological underpinnings due to the complex phenotypes of violence [ 7 , 41 ]. In addition, all the participants with VSC in the present study were free of substance abuse and personality disorder, thus, it is reasonable to infer that the brain structural alterations of these participants might be related to violence [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some other researchers found that patients with VSC had reduced GMV in the bilateral cerebellum, BA 39/40 [ 11 ], putamen, left cuneus/precuneus and parietal cortex [ 18 ], as well as decreased cortical thickness in sensorimotor regions [ 19 ], compared to those with NSC. However, some neuroimaging studies did not find any significant difference in the brain structure between the VSC and NSC [ 7 , 15 , 20 , 21 ]. Due to the disparities in current findings, the structural changes associated with violence in SCZ are still unclear, nor is its association with clinical risk factors in SCZ, which indicated the necessity to explore the neurobiological underpinning of violent behavior in individuals with SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Patienten, die an Schizophrenie leiden, haben ein erhöhtes Risiko, Gewalt gegen andere auszuüben und sind für etwa 10 % aller Tötungsdelikte verantwortlich 5 .…”
Section: Substanzmissbrauch Oder Krankheit?unclassified